Electrochemical and spectroscopic studies of the oxidation mechanism of the herbicide propanil - Garrido, E. Manuela (2014)
Electrochemical oxidation of propanil in deuterated solutions was studied by cyclic, differential pulse, and square wave voltammetry using a glassy carbon microelectrode. The oxidation of propanil in deuterated acid solutions occurs at the nitrogen atom of the amide at a potential of +1.15 V vs Ag/ AgCl. It was also found that, under the experimental conditions used, protonation at the oxygen atom of propanil occurs, leading to the appearance of another species in solution which oxidizes at +0.60 V. The anodic peak found at +0.79 V vs Ag/AgCl in deuterated basic solutions is related to the presence of an anionic species in which a negative charge is on the nitrogen atom. The electrochemical data were confirmed by the identification of all the species formed in acidic and basic deuterated solutions by means of NMR spectroscopy. The results are supported by electrochemical and spectroscopic studies of acetanilide in deuterated solutions.